Graphene aerogel for adsorption, magnetic recovery and photocatalytic regeneration and preparation method thereof
Patent Information
- Application Number
- CN202611212949.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
但现有复合气凝胶普遍功能集成度低,多仅具备“吸附+磁性”或“吸附+光催化”双重功能;少数涉及三重功能的材料也存在组分兼容性差、界面结合力弱、空间分布不均易团聚的问题,且缺乏对“吸附富集-光催化降解”协同机制的系统设计,多次循环后功能组分易脱落,材料性能衰减明显,难以满足工程化应用需求
1.功能高度集成,协同效应显著:将吸附、磁性回收、光催化再生三重功能集成于单一石墨烯气凝胶材料,构建“吸附富集-光催化降解-磁性分离”的一体化水处理模式。吸附富集可提升光催化效率,光催化可原位释放吸附位点,磁性分离可实现材料便捷回收,三者协同提升整体处理性能。
Smart Images

Figure CN122999138A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental functional materials technology, specifically relating to an adsorption, magnetic recovery and photocatalytic regeneration graphene aerogel and its preparation method. Background Technology
[0002] With the acceleration of industrialization and urbanization, water pollution has become increasingly severe. Recalcitrant pollutants in industrial wastewater from dyeing, pharmaceuticals, and heavy metals pose a serious threat to the ecological environment and human health. Adsorption methods are widely used in water pollution control due to their simplicity, low cost, and high efficiency. Graphene aerogels, with their ultra-high specific surface area, three-dimensional interconnected porous structure, and abundant surface functional groups, have become a research hotspot in water treatment adsorption materials.
[0003] However, existing graphene aerogel adsorbents still face three major bottlenecks in practical applications: First, recovery in powder form is difficult. Most graphene-based adsorbents are nanoparticles, which are difficult to separate efficiently after adsorption, easily causing secondary pollution. Separation methods such as filtration and centrifugation are energy-intensive and require sophisticated equipment. Second, regeneration costs are high after adsorption saturation. Organic solvent extraction, high-temperature calcination, or chemical elution are usually required, which are energy-intensive, complex to operate, and can easily damage the material structure. Third, they only achieve phase transfer of pollutants and cannot completely mineralize and degrade them. Materials after adsorption saturation still need to be disposed of as hazardous waste, posing a risk of secondary pollution.
[0004] To address these issues, existing technologies propose two modification directions: one is to introduce magnetic nanoparticles such as Fe3O4 to impart magnetic separation properties to the material; the other is to load photocatalysts such as TiO2 and BiOBr to achieve pollutant degradation. However, existing composite aerogels generally have low functional integration, mostly possessing only dual functions of "adsorption + magnetism" or "adsorption + photocatalysis"; the few materials involving triple functions also suffer from poor component compatibility, weak interfacial bonding, uneven spatial distribution, and easy aggregation. Furthermore, they lack a systematic design for the synergistic mechanism of "adsorption enrichment-photocatalytic degradation," and functional components are prone to detachment after multiple cycles, resulting in significant material performance degradation and making it difficult to meet the needs of engineering applications. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide an adsorption, magnetic recovery, and photocatalytic regeneration graphene aerogel and its preparation method that integrate adsorption, magnetic recovery, and photocatalytic regeneration functions, achieving a high degree of integration and synergistic effect of the three functions, and improving the material's cycle stability.
[0006] This invention is achieved through the following technical solution: An adsorption, magnetic recovery, and photocatalytic regeneration graphene aerogel includes a three-dimensional porous reduced graphene oxide aerogel framework, and magnetic nanoparticles and photocatalytic nanoparticles anchored on the graphene aerogel framework. The magnetic nanoparticles are functionalized particles with active functional groups on their surface, fixed to the graphene sheet surface and interlayer pores via chemical bonding. The photocatalytic nanoparticles are fixed to the graphene sheet surface and interlayer pores via physical loading or chemical bonding. The magnetic nanoparticles and photocatalytic nanoparticles are dispersed in the hierarchical porous structure of the aerogel. In the hierarchical porous structure, micropores with a pore size less than 2 nm account for 5%–15% of the total pore volume, mesopores with a pore size of 2–50 nm account for 40%–60% of the total pore volume, and macropores with a pore size greater than 50 nm account for 30%–50% of the total pore volume. The micropores provide numerous active sites for pollutant adsorption, ensuring high adsorption capacity of the material; the mesopores provide mass transfer channels between pollutants and photoactive free radicals, shortening the mass transfer distance and improving photocatalytic degradation efficiency; the macropores provide macroscopic flow paths for water, reducing flow resistance and adapting to continuous flow dynamic water treatment scenarios. The three levels of pores work together to achieve efficient coupling of adsorption enrichment and photocatalytic degradation.
[0007] Furthermore, the three-dimensional porous graphene aerogel framework is a reduced graphene oxide aerogel with a specific surface area of 300–1000 m² / g, a porosity of 85%–98%, and a pore size of 10 nm–50 μm, forming a hierarchical porous structure of micropores, mesopores, and macropores.
[0008] Furthermore, the magnetic nanoparticles are selected from one or more of Fe3O4, γ-Fe2O3, CoFe2O4, and MnFe2O4, with a particle size of 5-50 nm and a mass fraction of 5%-30% in the aerogel. The magnetic nanoparticles adopt a Fe3O4@SiO2 core-shell structure. The SiO2 shell can isolate the magnetic core from the reaction system, avoiding secondary pollution caused by the dissolution of magnetic ions. At the same time, the SiO2 surface is rich in hydroxyl groups, which makes it easier to introduce active functional groups through silane coupling agents, strengthen the chemical bonding strength between the magnetic particles and the graphene framework, and further improve the structural stability of the material during recycling.
[0009] Furthermore, the photocatalytic nanoparticles are selected from one or more of TiO2, BiOBr, BiOCl, g-C3N4, ZnO, and CdS, with a particle size of 5-100 nm and a mass fraction of 5%-25% in the aerogel.
[0010] Furthermore, the magnetic nanoparticles are Fe3O4@SiO2 core-shell structured nanoparticles, with a SiO2 shell thickness of 2–10 nm.
[0011] Furthermore, carbon nanotubes or nanocellulose are incorporated into the graphene aerogel framework as a mechanical reinforcing phase.
[0012] A method for preparing graphene aerogel by adsorption, magnetic recovery, and photocatalytic regeneration includes the following steps: S1: Preparation and surface functionalization of magnetic nanoparticles S1.1: Preparation of Fe3O4 magnetic nanoparticles by solvothermal method: Iron salt, sodium acetate and dispersant were dissolved in ethylene glycol, stirred evenly and then transferred to a hydrothermal reactor. The reaction was carried out at 200℃ for 8-12 h. The product was obtained by magnetic separation, washing and drying. S1.2: SiO2 shell coating: Fe3O4 nanoparticles were dispersed in an ethanol-water mixed solution and ultrasonically dispersed until uniform. Ammonia was added to adjust the pH of the system to 8-9. Tetraethyl orthosilicate was slowly added dropwise and stirred at 25-40℃ for 4-8 hours. A SiO2 shell was formed on the surface of Fe3O4 particles through the hydrolysis-condensation reaction of tetraethyl orthosilicate. After the reaction, magnetic separation and washing were performed to obtain Fe3O4@SiO2 core-shell structured nanoparticles. S1.3: Surface functionalization modification: Fe3O4@SiO2 core-shell particles were dispersed in anhydrous ethanol, a silane coupling agent was added, and the mixture was refluxed at 60-80℃ for 4-6 hours to introduce amino or thiol active functional groups on the particle surface, thus obtaining surface-functionalized magnetic nanoparticles.
[0013] S2: Preparation of photocatalytic nanoparticles: Nanoscale, highly crystalline photocatalytic nanoparticles were prepared; S3: Preparation of graphene oxide aqueous dispersion: Graphene oxide aqueous dispersion was prepared using the modified Hummers method. Construction of S4 three-dimensional magnetic graphene hydrogel: The surface-functionalized magnetic nanoparticles obtained in step S1 are dispersed in deionized water to form a surface-functionalized magnetic nanoparticle dispersion; the dispersion is mixed evenly with the graphene oxide aqueous dispersion obtained in step S3, and the graphene oxide is reduced and self-assembled through hydrothermal reaction to form a three-dimensional magnetic graphene hydrogel. S5 In-situ loading of photocatalytic nanoparticles: The three-dimensional magnetic graphene hydrogel obtained in step S4 is immersed in the photocatalytic nanoparticle dispersion in step S2, so that the photocatalytic nanoparticles are loaded on the inner surface of the hydrogel pores. Unloaded particles are washed away to obtain an integrated hydrogel. S6 Solvent replacement and drying: The integrated hydrogel obtained in step S5 is subjected to solvent replacement and then dried to obtain an aerogel; S7 Post-treatment: The dried aerogel is subjected to thermal reduction treatment under a nitrogen atmosphere.
[0014] Further, in step S1, the magnetic nanoparticles are prepared by a solvothermal method: FeCl3・6H2O, NaAc and polyethylene glycol are dissolved in ethylene glycol and reacted at 200°C to obtain Fe3O4 nanoparticles; then the Fe3O4 nanoparticles are dispersed in anhydrous ethanol and KH550 is added to react to obtain amino-functionalized Fe3O4 nanoparticles.
[0015] Further, in step S2: when the photocatalytic nanoparticles are BiOBr nanosheets, Bi(NO3)3・5H2O is ultrasonically dissolved in ethylene glycol, and KBr is added before hydrothermal reaction at 180°C to obtain the nanosheets; when the photocatalytic nanoparticles are g-C3N4 nanosheets, melamine or urea is calcined at 550°C to obtain block g-C3N4, which is then obtained by thermal oxidation etching or liquid phase exfoliation.
[0016] Furthermore, in step S4, the hydrothermal reaction temperature is 120–200°C, and the reaction time is 6–24 hours; in step S6, anhydrous ethanol or tert-butanol is used for solvent replacement, and the drying method is freeze drying or supercritical CO2 drying; in step S7, the thermal reduction temperature is 200–400°C, and the treatment time is 2–6 hours.
[0017] The beneficial effects of this invention are: 1. Highly integrated functions and significant synergistic effects: Adsorption, magnetic recovery, and photocatalytic regeneration are integrated into a single graphene aerogel material, constructing an integrated water treatment mode of "adsorption enrichment - photocatalytic degradation - magnetic separation". Adsorption enrichment can improve photocatalytic efficiency, photocatalysis can release adsorption sites in situ, and magnetic separation can realize convenient material recovery. The three synergistically improve the overall treatment performance.
[0018] Uniform dispersion and stable bonding: Through a process combining surface functionalization modification and hydrothermal self-assembly, magnetic nanoparticles and photocatalytic nanoparticles are uniformly dispersed and stably anchored in the graphene framework, effectively avoiding particle agglomeration and detachment, resulting in high magnetic separation recovery rate; The Fe3O4@SiO2 core-shell structure, on the one hand, protects the magnetic core through the SiO2 shell, inhibits the dissolution of iron ions under acidic conditions, and improves the environmental adaptability of the material; on the other hand, it utilizes the abundant hydroxyl sites on the SiO2 surface to improve the grafting efficiency of silane coupling agents, further enhancing the interfacial bonding force between magnetic particles and the graphene framework, and reducing the risk of particle detachment during cycling.
[0019] 2. In-situ self-regeneration and low operating cost: Breaking through the limitations of traditional adsorption materials’ “adsorption-transfer”, it achieves complete mineralization of pollutants and in-situ regeneration of materials through photocatalysis, eliminating the need for chemical elution and high-temperature treatment, and generating no secondary waste liquid, which can significantly reduce operating costs and hazardous waste disposal volume.
[0020] 3. Simple separation operation and strong engineering adaptability: Magnetic separation does not require filtration or centrifugation equipment, has low energy consumption and is easy to operate; by introducing a mechanically enhanced phase, it can also be adapted to continuous flow dynamic water treatment scenarios, and has a wide range of engineering applications.
[0021] 4. Excellent cycle performance and long service life: After multiple adsorption-photocatalytic cycles, the material retains a high adsorption capacity and has stable magnetic recovery performance, exhibiting good long-term stability. Attached Figure Description
[0022] The present invention will now be described in further detail with reference to the accompanying drawings.
[0023] Figure 1 This is a schematic diagram of the multifunctional synergistic mechanism of the integrated graphene aerogel material of the present invention, which involves "adsorption-magnetic recovery-photocatalytic regeneration". Figure 2 This is a process flow diagram of the integrated graphene aerogel preparation method of the present invention; Figure 3 This is a comparison chart of the adsorption and removal rates of different pollutants by the material in Example 1 of the present invention; Figure 4 This is a photocatalytic degradation curve of o-nitrophenol using the material from Example 1 of this invention; Figure 5 The graph shows the cyclic stability test results of the material in Example 1 of this invention. Detailed Implementation
[0024] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.
[0025] It should be noted that the terms “comprising,” “including,” or any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0026] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The adsorption-magnetic recovery-photocatalytic regeneration multifunctional synergistic mechanism of the present invention is as follows: Figure 1 As shown, the preparation process of the integrated graphene aerogel is as follows: Figure 2 As shown.
[0027] Unless otherwise specified, all experimental reagents used in the following examples are commercially available analytical grade reagents, and the experimental water is deionized water with a resistivity ≥18.2 MΩ・cm. All experimental equipment used is conventional experimental equipment in the field, and the following are exemplary commonly used models: hydrothermal synthesis reactor is KH-100 type polytetrafluoroethylene lined stainless steel reactor; high-speed centrifuge is TG16-WS type benchtop high-speed centrifuge; ultrasonic cleaner is KQ-250DE type CNC ultrasonic cleaner; vacuum drying oven is DZF-6050 type vacuum drying oven; vacuum freeze dryer is LGJ-10 type; supercritical CO2 drying device is HA221-40-11 type; box-type resistance furnace (muffle furnace) is SX2-4-10 type; xenon lamp light source is CEL-HXF300 type, equipped with a 420nm cutoff filter to obtain visible light.
[0028] Example 1: Fe3O4 / BiOBr co-modified integrated graphene aerogel (I) Material Preparation S1: Preparation and Functionalization of Fe3O4@SiO2 Magnetic Nanoparticles S1.1: Dissolve 2.7g FeCl3・6H2O, 7.2g NaAc and 2.0g PEG-2000 in 80mL ethylene glycol, stir well and transfer to a 100mL polytetrafluoroethylene-lined hydrothermal reactor. React at 200℃ for 12h. Separate the product with a magnet, wash three times with anhydrous ethanol, and dry under vacuum at 60℃ to obtain Fe3O4 nanoparticles with a particle size of about 15nm. S1.2: 0.5 g of Fe3O4 nanoparticles were dispersed in a mixed solution of 80 mL anhydrous ethanol and 20 mL deionized water, and ultrasonically dispersed for 30 min. 2 mL of concentrated ammonia was added to adjust the pH of the system to 8.5, and 0.3 mL of tetraethyl orthosilicate was slowly added dropwise. The mixture was stirred at 30 °C for 6 h. After the reaction was completed, the product was collected by magnetic separation and washed three times with alternating ethanol and deionized water to obtain Fe3O4@SiO2 core-shell nanoparticles. TEM characterization showed that the SiO2 shell thickness was approximately 5 nm. S1.3: The above Fe3O4@SiO2 particles were dispersed in 50 mL of anhydrous ethanol, 1 mL of KH550 was added, and the mixture was refluxed at 60 °C for 6 h. After magnetic separation and washing, amino-functionalized Fe3O4@SiO2 magnetic nanoparticles were obtained.
[0029] S2: Preparation of BiOBr photocatalytic nanosheets: 0.97 g Bi(NO3)3・5H2O was ultrasonically dissolved in 20 mL ethylene glycol, and 0.238 g KBr dissolved in 20 mL deionized water was added. After stirring for 30 minutes, the mixture was transferred to a hydrothermal reactor and reacted at 180 °C for 12 hours. The product was collected by centrifugation at 8000 rpm, washed three times alternately with deionized water and ethanol, and dried at 60 °C to obtain BiOBr nanosheets with a thickness of approximately 15 nm and a lateral dimension of 200–400 nm.
[0030] S3: Preparation of graphene oxide aqueous dispersion: Graphene oxide was prepared using the modified Hummers method and formulated into an aqueous dispersion of 6 mg / mL.
[0031] S4: Construction of magnetic graphene hydrogel: 100 mg of amino-functionalized Fe3O4 was ultrasonically dispersed in 20 mL of deionized water and mixed with 60 mL of GO aqueous dispersion. The mixture was ultrasonically dispersed for 30 minutes. The mixture was then transferred to a hydrothermal reactor and reacted at 180 °C for 12 hours to obtain Fe3O4 / rGO magnetic hydrogel.
[0032] S5: In-situ loading of BiOBr: Fe3O4 / rGO magnetic hydrogel was immersed in 100 mL of BiOBr dispersion with a concentration of 1 mg / mL and ultrasonically assisted for 4 hours; after removal, it was washed with deionized water to remove unloaded BiOBr.
[0033] S6: Solvent replacement and drying: The integrated hydrogel was replaced with tert-butanol three times, each time for 12 hours; then supercritical CO2 drying was performed to obtain Fe3O4 / BiOBr co-modified integrated graphene aerogel.
[0034] (ii) Performance Testing Adsorption performance test: 20 mg of integrated graphene aerogel was added to 100 mL of 10 mg / L o-nitrophenol solution, 50 mg / L Cr(VI) solution, and 20 mg / L tetracycline hydrochloride solution, respectively, and adsorbed in the dark for 120 minutes. The removal rate of o-nitrophenol was measured to be 96.5%, with a Langmuir fitted maximum adsorption capacity of approximately 450 mg / g; the removal rate of Cr(VI) was 92.3%; and the removal rate of tetracycline hydrochloride was 89.7%. The adsorption and removal effects of different pollutants are shown in the figure. Figure 3 As shown.
[0035] Magnetic separation performance test: After adsorption was completed, a strong magnet was placed on the side wall of the container. The aerogel aggregated towards the magnet within 30 seconds, and the solution rapidly changed from colored to clear and transparent. The magnetic separation recovery rate was calculated to be 98.2% by weight.
[0036] The pore structure parameters were tested using a specific surface area and pore size analyzer. The specific surface area, pore size distribution of micropores and mesopores, and pore volume ratio of the material were determined by nitrogen adsorption-desorption method. The distribution of macropores larger than 50 nm was characterized by mercury porosimetry. The aerogel in this embodiment had a specific surface area of 862 m² / g and a porosity of 93.5%. The pore volume distribution was as follows: micropores accounted for 8.2%, mesopores accounted for 52.7%, and macropores accounted for 39.1%, forming a typical hierarchical porous structure.
[0037] Photocatalytic degradation performance test: 50 mg of integrated graphene aerogel was placed in 100 mL of o-nitrophenol solution with a concentration of 20 mg / L. After adsorption in the dark for 60 minutes to reach equilibrium, visible light irradiation was performed using a 300W xenon lamp with a 420 nm cutoff filter. The degradation rate exceeded 80% after 120 minutes of irradiation and exceeded 98% after 180 minutes of irradiation. The visible light photocatalytic degradation curve of o-nitrophenol is shown below. Figure 4 As shown.
[0038] Cyclic stability test: The same aerogel sample was subjected to five cycles of "adsorption-photocatalytic degradation-magnetic recovery," with each cycle consisting of 120 minutes of adsorption and 120 minutes of photocatalytic regeneration. After five cycles, the aerogel retained 85.5% of its adsorption capacity for o-nitrophenol, and the magnetic recovery rate remained above 95%. The performance changes of the material after recycling are shown below. Figure 5 As shown.
[0039] Example 2: Fe3O4 / g-C3N4 co-modified integrated graphene aerogel The only difference between this embodiment and Example 1 is that g-C3N4 nanosheets are used instead of BiOBr nanosheets in step S2. Preparation of g-C3N4 nanosheets: 10g of urea was placed in a covered porcelain crucible, placed in a box-type resistance furnace, and calcined at 550℃ for 4 hours to obtain blocky g-C3N4; after grinding, it was again thermally oxidized and etched at 500℃ for 2 hours to obtain g-C3N4 nanosheets with a thickness of 3-5nm.
[0040] Testing showed that the aerogel in this embodiment exhibited a maximum Langmuir adsorption capacity of approximately 420 mg / g for o-nitrophenol and approximately 380 mg / g for tetracycline hydrochloride. After 90 minutes of visible light irradiation, the degradation rate of o-nitrophenol reached 90.5%. The magnetic separation recovery rate was greater than 97%, and the adsorption capacity retention rate after 5 cycles was approximately 84%. Furthermore, it maintained stable photocatalytic activity over a wide pH range. The aerogel in this embodiment had a specific surface area of 795 m² / g and a porosity of 92.1%. The pore volume distribution was as follows: micropores accounted for 7.6%, mesopores for 49.3%, and macropores for 43.1%.
[0041] Example 3: CNTs-enhanced integrated graphene aerogel The only difference between this embodiment and Example 1 is that carboxylated multi-walled carbon nanotubes are added to the hydrothermal reaction system in step S4, with a GO to CNT mass ratio of 10:1. The carbon nanotubes used are commercially available products in the art, with a diameter of 10–20 nm, a length of 5–15 μm, and a carboxyl content of approximately 2.0 wt%.
[0042] Tests showed that the compressive strength of the aerogel in this embodiment is approximately 2.5 times that of Example 1; the volume shrinkage rate after 5 cycles is less than 8%, indicating a significant improvement in structural stability and making it more suitable for continuous flow dynamic water treatment scenarios; the specific surface area of the aerogel in this embodiment is 827 m² / g, and the porosity is 94.2%; the pore volume distribution is as follows: micropores account for 9.1%, mesopores account for 54.6%, and macropores account for 36.3%.
[0043] Comparative Example 1: Non-magnetic BiOBr / rGO aerogel The preparation method is basically the same as in Example 1, except that Fe3O4 magnetic nanoparticles are not prepared or loaded in step S1. This material possesses photocatalytic degradation capabilities, but after adsorption saturation, it requires filtration or centrifugation, which is cumbersome, results in low recovery rates, and the material is easily damaged and lost during the recovery process.
[0044] Comparative Example 2: Photocatalytic-free Fe3O4 / rGO magnetic aerogel The preparation method is basically the same as in Example 1, except that BiOBr photocatalytic nanoparticles are not prepared or loaded in step S2. This material can be rapidly separated by a magnetic field, but it has no in-situ regeneration capability. After adsorption saturation, it needs to be regenerated by chemical elution. After multiple cycles, the adsorption capacity decreases significantly, and the elution waste liquid requires additional treatment, which can easily cause secondary pollution.
[0045] A comparison of Examples 1-3 with Comparative Examples 1-2 shows that the present invention, by uniformly anchoring magnetic nanoparticles and photocatalytic nanoparticles in a reduced graphene oxide aerogel framework, enables the material to simultaneously possess the triple functions of efficient adsorption and enrichment, rapid separation and recovery under an external magnetic field, and in-situ regeneration via visible light photocatalysis. Compared to Comparative Example 1, which only loads photocatalytic components, the material of the present invention can achieve rapid solid-liquid separation via a magnetic field, resulting in high recovery rates, simple operation, and avoiding material loss and secondary pollution. Compared to Comparative Example 2, which only loads magnetic components, the material of the present invention can achieve in-situ regeneration via photocatalytic degradation, eliminating the need for chemical elution, maintaining good performance after multiple cycles, and reducing operating costs. Example 3, which incorporates carbon nanotube reinforcement, further enhances the mechanical strength and structural stability of the material, making it more suitable for engineering water treatment scenarios such as continuous flow.
[0046] The scope of protection of this invention is not limited to the technical solutions disclosed in the specific embodiments. Any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of this invention shall fall within the scope of protection of this invention.
Claims
1. A graphene aerogel that is adsorbed, magnetically recovered, and photocatalytically regenerated, characterized in that: The aerogel comprises a three-dimensional porous reduced graphene oxide aerogel framework, and magnetic nanoparticles and photocatalytic nanoparticles anchored on the graphene aerogel framework. The magnetic nanoparticles are functionalized particles with active functional groups on their surfaces, which are fixed to the surface of the graphene sheets and the interlayer pores by chemical bonding. The photocatalytic nanoparticles are fixed to the surface of the graphene sheets and the interlayer pores by physical loading or chemical bonding. The magnetic nanoparticles and photocatalytic nanoparticles are dispersed in the hierarchical porous structure of the aerogel.
2. The graphene aerogel with adsorption, magnetic recovery, and photocatalytic regeneration according to claim 1, characterized in that: The three-dimensional porous graphene aerogel framework is a reduced graphene oxide aerogel with a specific surface area of 300–1000 m² / g and a porosity of 85%–98%. The aerogel forms a hierarchical porous structure of micropores, mesopores, and macropores, with a pore size distribution range of 1 nm–50 μm. Among them, the micropore volume accounts for 5%–15% of the total pore volume, the mesopore volume accounts for 40%–60% of the total pore volume, and the macropore volume accounts for 30%–50% of the total pore volume.
3. The graphene aerogel with adsorption, magnetic recovery, and photocatalytic regeneration according to claim 1, characterized in that: The magnetic nanoparticles are selected from one or more of Fe3O4, γ-Fe2O3, CoFe2O4, and MnFe2O4, with a particle size of 5-50 nm and a mass fraction of 5%-30% in the aerogel.
4. The graphene aerogel with adsorption, magnetic recovery, and photocatalytic regeneration according to claim 1, characterized in that: The photocatalytic nanoparticles are selected from one or more of TiO2, BiOBr, BiOCl, g-C3N4, ZnO, and CdS, with a particle size of 5-100 nm and a mass fraction of 5%-25% in the aerogel.
5. The graphene aerogel with adsorption, magnetic recovery, and photocatalytic regeneration according to claim 1, characterized in that: The magnetic nanoparticles are Fe3O4@SiO2 core-shell structured nanoparticles, with Fe3O4 as the magnetic core and SiO2 as the coating shell, and the SiO2 shell thickness is 2-10 nm.
6. The graphene aerogel with adsorption, magnetic recovery, and photocatalytic regeneration according to claim 1, characterized in that: The graphene aerogel framework is also doped with carbon nanotubes or nanocellulose as mechanical reinforcement phases.
7. A method for preparing graphene aerogel by adsorption, magnetic recovery, and photocatalytic regeneration according to any one of claims 1 to 6, characterized in that: Includes the following steps: S1: Preparation and surface functionalization of magnetic nanoparticles S1.1: Preparation of Fe3O4 magnetic nanoparticles by solvothermal method: Iron salt, sodium acetate and dispersant were dissolved in ethylene glycol, stirred evenly and then transferred to a hydrothermal reactor. The reaction was carried out at 200℃ for 8-12 h. The product was obtained by magnetic separation, washing and drying. S1.2: SiO2 shell coating: Fe3O4 nanoparticles were dispersed in an ethanol-water mixed solution and ultrasonically dispersed until uniform. Ammonia was added to adjust the pH of the system to 8-9. Tetraethyl orthosilicate was slowly added dropwise and stirred at 25-40℃ for 4-8 hours. A SiO2 shell was formed on the surface of Fe3O4 particles through the hydrolysis-condensation reaction of tetraethyl orthosilicate. After the reaction, magnetic separation and washing were performed to obtain Fe3O4@SiO2 core-shell structured nanoparticles. S1.3: Surface functionalization modification: Fe3O4@SiO2 core-shell particles were dispersed in anhydrous ethanol, a silane coupling agent was added, and the mixture was refluxed at 60-80℃ for 4-6 hours to introduce amino or thiol active functional groups on the particle surface, thus obtaining surface-functionalized magnetic nanoparticles. 8.S2: Preparation of photocatalytic nanoparticles: Nanoscale, highly crystalline photocatalytic nanoparticles were prepared; S3: Preparation of graphene oxide aqueous dispersion: Graphene oxide aqueous dispersion was prepared using the modified Hummers method. Construction of S4 three-dimensional magnetic graphene hydrogel: The surface-functionalized magnetic nanoparticles obtained in step S1 are dispersed in deionized water to form a surface-functionalized magnetic nanoparticle dispersion; the dispersion is mixed evenly with the graphene oxide aqueous dispersion obtained in step S3, and the graphene oxide is reduced and self-assembled through hydrothermal reaction to form a three-dimensional magnetic graphene hydrogel. S5 In-situ loading of photocatalytic nanoparticles: The three-dimensional magnetic graphene hydrogel obtained in step S4 is immersed in the photocatalytic nanoparticle dispersion in step S2, so that the photocatalytic nanoparticles are loaded on the inner surface of the hydrogel pores. Unloaded particles are washed away to obtain an integrated hydrogel. S6 Solvent replacement and drying: The integrated hydrogel obtained in step S5 is subjected to solvent replacement and then dried to obtain an aerogel; S7 Post-treatment: The dried aerogel is subjected to thermal reduction treatment under a nitrogen atmosphere.
9. The method for preparing graphene aerogel by adsorption, magnetic recovery, and photocatalytic regeneration according to claim 7, characterized in that: In step S1, the magnetic nanoparticles are prepared by a solvothermal method: FeCl3・6H2O, NaAc and polyethylene glycol are dissolved in ethylene glycol and reacted at 200℃ to obtain Fe3O4 nanoparticles; then the Fe3O4 nanoparticles are dispersed in anhydrous ethanol and KH550 is added to react to obtain amino-functionalized Fe3O4 nanoparticles.
10. The method for preparing graphene aerogel by adsorption, magnetic recovery, and photocatalytic regeneration according to claim 7, characterized in that: In step S2: when the photocatalytic nanoparticles are BiOBr nanosheets, Bi(NO3)3・5H2O is ultrasonically dissolved in ethylene glycol, KBr is added, and a hydrothermal reaction is carried out at 180℃ to obtain the nanosheets; when the photocatalytic nanoparticles are g-C3N4 nanosheets, melamine or urea is calcined at 550℃ to obtain bulk g-C3N4, which is then obtained by thermal oxidation etching or liquid phase exfoliation.
11. The method for preparing graphene aerogel by adsorption, magnetic recovery, and photocatalytic regeneration according to claim 7, characterized in that: In step S4, the hydrothermal reaction temperature is 120–200℃ and the reaction time is 6–24 hours; in step S6, anhydrous ethanol or tert-butanol is used for solvent replacement, and the drying method is freeze drying or supercritical CO2 drying; in step S7, the thermal reduction temperature is 200–400℃ and the treatment time is 2–6 hours.
